First Korean Case of DOK7 Congenital Myasthenic Syndrome Responsive to Ephedrine Therapy - Sangwon Joe; Moonjeong Choi; Yunjung Choi; Soo-Hyun Kim; Hyung Jun Park (Journal of Electrodiagnosis and Neuromuscular Diseases, 2026)
Congenital myasthenic syndromes (CMSs) are a heterogeneous group of genetic neuromuscular disorders caused by pathogenic variants in genes encoding proteins essential for neuromuscular junction development and function. Downstream of tyrosine kinase 7 (DOK7)-related CMS has been reported frequently in Europe, North America, and Japan, but not in Korea. A 7-year-old girl presented with gait disturbance, frequent falls, and difficulty climbing stairs, which had begun at 4 years of age. Examination revealed mild symmetric proximal weakness without ocular or bulbar involvement, and her serum creatine kinase level was normal. She was initially diagnosed with congenital myopathy. At 24 years of age, whole-exome sequencing identified compound heterozygous pathogenic variants in DOK7 (c.[539G>C];[1124_1127dup]), confirming DOK7 CMS. On clinical re-evaluation, she had stable proximal weakness, and repetitive nerve stimulation demonstrated a significant decremental response in the trapezius muscle. After 1 month of oral ephedrine therapy at 50 mg/day, her endurance and stair-climbing ability improved substantially. We report the first Korean case of DOK7 CMS with a favorable therapeutic response to ephedrine, emphasizing the need to consider CMS in the differential diagnosis of congenital myopathy.